Uniri Digital Library – Supporting Open Science at the University of Rijeka - Branka Turk; Ivana Dorotić Malič; Sandra Cuculić (Bosniaca)
Goal: The main objective of this paper is to investigate, analyse and present how the Uniri Digital Library is organised. Methodology: The paper gives an overview of important activities which the University of Rijeka Library has in cooperation with the University of Rijeka and the University constituents2 taken to increase the number of objects stored and published in the institutional repositories. Results: The paper analyses digital objects stored and published in the Uniri Digital Library by the type of papers and openness. The analysis has identified insufficient openness of objects in spite of legal regulations and storage obligations on the national and institutional levels. Data suggests that it is necessary to establish new evaluation and reward system in implementing the practices of open science, but also to continuously perform education and raise awareness about the importance of open scientific information. Originality: The paper presents the theoretical concept and the legal framework for the establishment of the Uniri Digital Library. Until the adoption of the Digital Library Standard, the Uniri Digital Library was called University of Rijeka3 Repository.